ANALISIS KEBUTUHAN PENGEMBANGAN BAHAN AJAR BERBASIS MULTI REPRESENTASI UNTUK MENINGKATKAN KOMPETENSI GURU FISIKA - Diah Mulhayatiah; Parlindungan Sinaga; Rizki Hidayatulloh (JURNAL SPEKTRA, 2022)
Every teacher must have four competencies, namely personality competence, pedagogic competence, social competence, and professional competence. The four competencies enable teachers to create ideal physics learning activities. One way that teachers can do to improve their competence is by participating in training and education activities. However, the location and time that teachers have often makes it difficult for them to participate in these activities. Teaching materials are needed that are packaged interactively and can be used by teachers independently without direction from a facilitator, one of which is by developing multi-representation-based teaching materials. This study aims to analyze the urgency of multi-representation-based teaching materials to improve the competence of physics teachers. The method used in this study is a qualitative method by conducting a literature study from various references both on a national and international scale. The results obtained indicate that multi-representation plays an important role in learning physics, both in improving learning outcomes, cognitive abilities, and problem solving abilities. In addition, the use of multi-representation-based teaching materials also always improves the aspects that you want to improve. This means that multi-representation teaching materials can also be developed to improve the competence of physics teachers